Rest times of Panicum maximum and Brachiaria brizantha through three types of cutting - Lucero Pita, Josselyn (2023)
The aim of this study was to determine the rest time of Savoy grass (Panicum maximum) and Brachiaria (Brachiaria brizanta) with three types of equalization cut and four rest times or days after the equalization cut. The research was carried out in Luz de América, Santo Domingo de los Tsáchilas province, Ecuador, during the dry season. The pastures were 7 years old, and the study factors were the grass varieties (Saboya and Brachiaria), types of cut (Machete, Scythe and Tractor) and days after the equalization cut (21, 28, 35 and 42 days). In total, 24 treatments with four repetitions each. The same management was carried out in all treatments (weed control, fertilization and initial cutting). Data collection was weekly, from days 21 to 42, using a quadrant of 1 m2. Plant height, green matter production, dry matter yield, bromatological analysis (protein, fat, ash, fibre and nitrogen-free extract) were evaluated. The results indicated that the peak of production of green matter and dry matter and height of the plant in the two varieties was on day 35; likewise, it was confirmed that the maximum cutting time of the pastures should be done until day 35, because the nutritional values tend to decrease with the age of the pasture. The Brachiaria variety cut with a tractor at 28 days, expressed the best nutritional contents of the grass, being therefore identified as the best forage option for the area in the dry season.